Myricetin Ameliorates Brain Damage Induces by Cerebral Ischemia-Reperfusion Injury in Rats - Khaleq, Maysaa Ali Abdul (Asian Journal of Pharmaceutics (AJP), 2020)
Background: Interruption of blood flow may result in considerable tissue damage via ischemia/ reperfusion injury induced oxidative stress in brain tissues. The present study aimed to investigate the effects of myricetin treatment in rats cerebral I/R injury. Material and Methods: The study was carried out on 36 Wistar-albino rats, divided into four groups including Sham group, I/R group, I/R+(control-vehicle DMSO) and I/R+ myricetin 50 mg/kg intraperitoneally 1 hour before induction of ischemia. Measurement of brain tissue IL-1β, ICAM- 1, caspase-3, Notch 1 and jagged 1 was done after one hour of reperfusion with assessment of the brain infarcted area and histopathological analysis. Results: Myricetin attenuates the cerebral I/R injury induced increase in inflammatory cytokine (IL-1β), adhesion molecule (ICAM-1) and proapoptotic enzyme (caspase-3). Additionally, it reduces the size of infarcted area and histopathological damage. However, such protective effect was not found to be mediated by Notch 1 pathway because myricetin treatment didn’t show changes in the increased levels of Notch 1 and Jagged 1 seen in brain with I/R injury. Conclusions: Myricetin has a neurocytoprotective effect against cerebral I/R injury which is manifested as anti-inflammatory anti-apoptotic preserving cell structure and viability, nevertheless this effect is not mediated through Notch 1 pathway.